Knowledge and attitudes of adult HIV positive patients to HIV/AIDS in Selected ART Clinics in Yola, Nigeria - Martins, Olutayo Folashade; Gyanchand Rampal, Lekhraj Rampal; Lye, Munn Sann; Mohd Sidik, Sherina; Othman, Norlijah; Iliyasu, Zubairu; Salawu, Fatai Kunle (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2015)
Though cases of AIDS are visible in Nigeria and awareness of HIV is high, correct knowledge on HIV transmission and prevention has remained low with significant numbers of people living with HIV/AIDS having low attitudes towards life and the disease itself. This study determined the baseline knowledge on HIV transmission and prevention, and attitudes towards HIV/AIDS of adult HIV positive patient enrolled into care at all four comprehensive antiretroviral therapy (ART) sites in Yola, Nigeria. Baseline reports on the knowledge and attitudes of adult HIV positive patients were obtained from a three arm randomized single blind clinical trial involving 386 randomly selected adult HIV patients who were enrolled into ART care at all four comprehensive ART sites in Yola. An administered, validated structured questionnaire was used for data collection. Outcome measures were sound knowledge on HIV transmission and prevention, and attitudes towards HIV/AIDS. Data was analyzed using SPSS version 22. Test of significance was at α level 0.05. Overall 237 (61.4%) had sound knowledge on HIV transmission and prevention, while 346 (89.6%) of respondents had high attitudes towards HIV/AIDS. Though majority of respondents had sound knowledge on HIV transmission and prevention as well as high attitudes towards HIV/AIDS, interventions to improve knowledge and attitudes among this group of individuals would improve positive preventive strategies.